2012
DOI: 10.1021/ml300229y
|View full text |Cite
|
Sign up to set email alerts
|

Bivalent Ligands Targeting Multiple Pathological Factors Involved in Alzheimer's Disease

Abstract: In a continuing effort to develop multifunctional compounds as potential treatment agents for Alzheimer’s disease (AD), a series of bivalent ligands containing curcumin and cholesterylamine were designed, synthesized, and biologically characterized. Biological characterization supported earlier results that the spacer length and its attachment position on curcumin are essential structural determinants for biological activity in this class. Compounds with a spacer length of 17 to 21 atoms exhibited optimal neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
42
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(53 citation statements)
references
References 31 publications
11
42
0
Order By: Relevance
“…As shown in Table 1, overall, the results of the six bivalent compounds are in agreement with our previous studies and show that compounds with 17-atom spacers are more potent than those with a 21-atom spacer (~ 3–6 times more potent). 29, 31 Specifically, 17MN and 21MN rescued MC65 cells with an EC 50 being 56.50 ± 9.08 and 212.28 ± 54.87 nM, respectively, consistent with our previously reported results. 31 Surprisingly, 21MO showed a significantly reduced potency (1848.67 ± 325.13 nM) compared our previously reported compound with a 21-atom spacer but different spacer composition.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…As shown in Table 1, overall, the results of the six bivalent compounds are in agreement with our previous studies and show that compounds with 17-atom spacers are more potent than those with a 21-atom spacer (~ 3–6 times more potent). 29, 31 Specifically, 17MN and 21MN rescued MC65 cells with an EC 50 being 56.50 ± 9.08 and 212.28 ± 54.87 nM, respectively, consistent with our previously reported results. 31 Surprisingly, 21MO showed a significantly reduced potency (1848.67 ± 325.13 nM) compared our previously reported compound with a 21-atom spacer but different spacer composition.…”
Section: Resultssupporting
confidence: 93%
“…29, 31 Specifically, 17MN and 21MN rescued MC65 cells with an EC 50 being 56.50 ± 9.08 and 212.28 ± 54.87 nM, respectively, consistent with our previously reported results. 31 Surprisingly, 21MO showed a significantly reduced potency (1848.67 ± 325.13 nM) compared our previously reported compound with a 21-atom spacer but different spacer composition. 33 This suggests that the nature of the spacer does play an essential role in the observed biological activities of these bivalent compounds.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…[12, 13] Our results demonstrated that the bivalent compounds exhibit significantly improved neuroprotection compared to the “war head” and the CM/LR anchor alone, or the combination of these two. Furthermore, we have demonstrated that the spacer length between the “war head” and the anchorage moiety is critical for neuroprotection.…”
Section: Introductionmentioning
confidence: 87%